Membangun kembali kepercayaan: Tantangan pemerintah dalam menjawab kritik publik secara demokratis - akbar, mohammad raihan (Maliki Interdisciplinary Journal, 2026)
Public trust is an important element in a democratic system because it influences the relationship between the government and society. In recent years, public criticism toward government policies has become more visible, especially through digital platforms and social media. This situation creates new challenges for the government in maintaining public trust while still respecting freedom of expression. This study aims to examine the challenges faced by the government in responding to public criticism in a democratic manner and to identify efforts that can help rebuild public confidence. The study uses a qualitative approach through library research by collecting information from scientific journals, reports, news articles, and other relevant references. The findings show that limited transparency, ineffective public communication, and slow government responses often lead to public disappointment. At the same time, the rapid growth of digital media allows criticism to spread quickly and shape public opinion on a large scale. The study also finds that openness to criticism, transparent policies, and more interactive communication can strengthen the relationship between the government and the public. Therefore, the government needs to develop a more democratic communication approach so that public criticism can be used as constructive input rather than being viewed as a political threat. In this way, public trust can grow through responsive attitudes, honest communication, and greater community involvement in policy-making processes.